Determinants of Waqf Interest among the Minangkabau Community: A Philantrepreneur Perspective - Zawawi, Abdul Azis Ahmad; Mariyanti, Tatik; Syofyan, Syofriza; Nawawi, Fathimah Ahmad Zawawi (Pandawan, 2024)
This research aims to analyze the influence of; knowledge, religiosity, culture, subjective norms, socialization, earnings on the Minangkabau Community interest in giving waqf, either directly or indirectly. The methodology uses in this research are using validity and reliability tests and analyz it using SEM (Structural Equation Modeling) with the help of SPSS and Microsoft Excel programs. The primary data for this research was obtained through a questionnaire survey of 400 respondents from the Minangkabau community who live in the West Sumatra region or outside the West Sumatra region. The results of this study show that the variables; knowledge, culture, socialization and earnings have a significant influence on the Minangkabau Community’s interest in giving waqf. Meanwhile, religiosity and subjective norms do not influence this. The research implicates that the role of good knowledge regarding waqf and supported by socialization based on Minangkabau Community Culture will have a positive impact on the Minangkabau Community interest in waqf.